Fungsi \( f:R \to R \) dan \( g: R \to R \) dinyatakan oleh \( f(x) = x+2 \) dan \( (g \circ f)(x) = 2x^2+4x+1 \). Maka \( g(2x) = \cdots \)
- \( 2x^2+4x+1 \)
- \( 2x^2-12x+1 \)
- \( 8x^2-8x+1 \)
- \( 8x^2+8x+1 \)
- \( 4x^2-8x+1 \)
Pembahasan:
Dari soal diketahui \( (g \circ f)(x) = 2x^2+4x+1 \), sehingga diperoleh berikut:
\begin{aligned} (g \circ f)(x) &= 2x^2+4x+1 \\[1em] g(f(x)) &= 2x^2+4x+1 \\[1em] g(x+2) &= 2(x+2)^2-4x-7 \\[1em] g(x+2) &= 2(x+2)^2-4(x+2)+1 \\[1em] g(x) &= 2x^2-4x+1 \\[1em] g(2x) &= 2(2x)^2-4(2x)+1 \\[1em] &= 8x^2-8x+1 \end{aligned}
Jawaban C.